2015
DOI: 10.14797/mdcj-11-4-228
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Hypertension: Mechanistic, Epidemiologic, and Treatment Parallels

Abstract: Atrial fibrillation (AF) is an increasingly prevalent condition and the most common sustained arrhythmia encountered in ambulatory and hospital practice. Several clinical risk factors for AF include age, sex, valvular heart disease, obesity, sleep apnea, heart failure, and hypertension (HTN). Of all the risk factors, HTN is the most commonly encountered condition in patients with incident AF. Hypertension is associated with a 1.8-fold increase in the risk of developing new-onset AF and a 1.5-fold increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 68 publications
(70 reference statements)
3
40
1
6
Order By: Relevance
“…Cardiac remodeling, especially the structural remodeling, is a key result of AF [2]. Cardiac fibroblasts activation and aberrant fibroblast signaling can lead to cardiac fibrosis and heart injury [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac remodeling, especially the structural remodeling, is a key result of AF [2]. Cardiac fibroblasts activation and aberrant fibroblast signaling can lead to cardiac fibrosis and heart injury [3].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, dramatic changes have occurred in how patients with AMI are diagnosed and treated. More sensitive troponin assays, early percutaneous revascularization and newer therapeutic options for medical management, have favorably reshaped the prognosis of patients with AMI [6]. Moreover, economic factors, including pay-for-performance and public reporting of adverse outcomes, as well as quality improvement programs have helped achieve better patient-related outcomes [7].…”
Section: Introductionmentioning
confidence: 99%
“…5 To better understand the causal pathway between hypertension and AF, researchers have examined relations between AF and state-of-the-art measures of arterial stiffness, wave reflection, pulsatile hemodynamic load, and endothelial dysfunction. Studies have reported that various measures of vascular structure and function [6][7][8][9] -including carotid-femoral pulse wave velocity (CFPWV), augmentation index, and central pulse pressure (CPP)-and measures of endothelial dysfunction, AF, as well as several other manifestations of cardiovascular disease.…”
mentioning
confidence: 99%